MENINGKATKAN ORAL HIGIENE DENGAN METODE DHE PADA ANAK DI KLINIK ILMU KEDOKTERAN GIGI ANAK RSGM UNIVERSITAS JEMBER - Sukanto Sukanto (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Dental caries continues to be the most common infectious disease in childhood. Improvement of oralhigiene is the strategy for preventing dental caries. This can be achieved by means of dental health education(DHE). This descriptive study purposed to evaluate the role of DHE on oral higiene status was measured by means ofGreen Vermillion Oral Higiene Index (OHI). The study was conducted during November 2010 –Januari 2011. OHIevaluation was performed at three time visit for every week interval. DHE was performed personslly, once, at the firstvisit, after evaluating OHI. The results showed that there were tendency of declining mean OHI after DHE treatment,both in boys and girls groups. In girls groups, at the first visit mean OHI =1,38. second visit OHI= 0,65 and third visit OHI =0,45, while for boys group, first visit mean OHI = 1,28, second visit OHI = 0,42 and third visit OHI = 0,35. It can beconcluded that personal DHE method improved oral higiene status, there for it was recomended that intensive DHEshould be performed as a routine clinical prosedure